Why Startups Fail: An Exploratory and Analytical Study - Abdelhak BADA; Abdelhadi BENGHALEM (Dirassat Journal Economic Issue, 2025)
This research aims to explore the reasons behind startup failures by reviewing founders' reports post-closure. To achieve this, the analytical method was adopted. The study concluded that startups often fail within the first few years due to a range of factors and challenges, including: offering a product or service that does not solve a market problem, running out of money and lack of funding, an unsuitable team, strong competition, cost and pricing issues, a poor business model, weak marketing and customer engagement, conflicts between founders, delays in keeping up with technology, lack of experience and passion, poor geographic location selection, legal challenges, delayed pivoting, incorrect pivoting, and lack of perseverance.